The Effects of Financial Performance towards Investment Return - Kanter, Abraham Bill; Siagian, Jonny (Universitas Kristen Indonesia, 2017)
Abstract: This research performed in order to test influence of fundamental factors towards investment return which measure by initial stock price price – ending stock price than divided by ending stock price in manufacturing company that listed in Indonesia stock exchange (IDX) during periode 2012-2015. The profitability ratio in this research was measured by return on asset, while leverage by Debt to equity ratio, and liquidity in this research used current ratio. The sample were collected using purposive sampling method and it has 61 companies for the resulting samples. The samples were analyzed using multiple linear regression technique. The result show that the ROA has negative and significant effect to investment return. While DER has positive and significant effect to investment return, and CR has positive and significant effect to investment return. Key words: Return on Asset, Debt to Equity Ratio, Current Ratio, Return investment